The Jewish-Greek tradition in antiquity and the Byzantine Empire - Aitken, J. K.; Paget, James Carleton; De Lange, Nicholas R. M. (Cambridge University Press, 2014)
"The Jewish-Greek tradition represents an arguably distinctive strand of Judaism characterized by use of the Greek language and interest in Hellenism. This volume traces the Jewish encounter with Greek culture from the earliest points of contact in antiquity to the end of the Byzantine Empire. It honors Nicholas de Lange, whose distinguished work brought recognition to an undeservedly neglected field, in part by dispelling the common belief that Jewish-Greek culture largely disappeared after 100 CE. The authors examine literature, archaeology, and biblical translations, such as the Septuagint, in order to illustrate the substantial exchange of language and ideas. The Jewish-Greek Tradition in Antiquity and the Byzantine Empire demonstrates the enduring significance of the tradition and will be an essential handbook for anyone interested in Jewish studies, biblical studies, ancient and Byzantine history, or the Greek language"--